Produção de Spodoptera frugiperda multiple nucleopolyedrovirus (SfMNPV) em lagartas de Spodoptera frugiperda (LEPIDOPTERA: NOCTUIDAE) : condições térmicas de inoculação e incubação - Soares, Carolina de Oliveira (2020)
Abstract: The biopesticids made by entomopathogens development has becoming an alternative to prague's control, but the inefficient production of viral polyhedras can limit the commercialization of inseticides based on virus. In the large scale production